Penerapan Zahir Accounting Versi 5.1 Dalam Penyusunan Laporan Keuangan Pada PT. Citarum Borneo Quantum - Sari, Dian Indah (Universitas Bina Sarana Informatika, 2019)
Abstract – Manually accounting processing has more risks than using a computerized system, because accounting requires a confidential database so all existing transactions are related to the finances of a company or individual entity. For example, in the simplest case, which is journal entry, it often occurs double input with the same number or voucher code for different transactions. This has an impact on the normal balance and financial statements that will be made. In order to collect data to fulfill the preparation of this application program, the authors conducted several ways, namely: Observation Method, This method is done by the author is to directly visit the location of the company and collect accounting transaction evidence and observe the process that has been running, so that the author can apply it to Zahir Accounting. Interview, the author conducted interviews with employees of PT. Citarum Borneo Quantum to obtain information on the history of the company, the process of recording accounting transactions from capital, sales, purchases, and financial statements. Library Study Method, carried out by reading books related to accounting transactions and related to the material of Programming Using Zahir Accounting Version 5.1. Based on the results of the discussion it can be concluded as follows: Application of Zahir Accounting Version 5.1 in preparing financial statements will produce computerized financial reports. The company was greatly helped by the application of Zahir Accounting Version 5.1 because it recorded financial transactions and financial reporting quickly, accurately and efficiently.Keywords: Zahir, Accounting, Financial Report